1990
DOI: 10.1093/cvr/24.8.665
|View full text |Cite
|
Sign up to set email alerts
|

Loss of blood platelet adhesion after heating native and cultured human subendothelium to 100  Celcius

Abstract: These in vitro results, if extrapolated to catheter interventions, suggest that thermal injury to the vessel wall by laser angioplasty or other thermal angioplasty methods may provide a basic and clinically relevant advantage over mechanical angioplasty modalities, because of a potentially reduced risk of complications related to platelet adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…No enhanced PA was found in the rabbit artery after heating it to 55°C. In this and previous in vitro studies [10,11] using human subendothelium, we found enhanced PA after heating to 55°C and this phenomenon therefore seems to be species-specific. In human specimens, we established that thermally denaturated von Willebrand factor in the subendothelium is responsible not only for a decrease in adhesion after exposure to temperatures high er than 71 °C, but also for an increase in adhesion after exposure to temperatures around 55 °C, provided the von Willebrand factor concentration is low [11], We tentative ly attribute the absence of an increase in adhesion to rab bit artery subendothelium to a high von Willebrand factor content in the subendothelium.…”
Section: Species Differencessupporting
confidence: 85%
See 1 more Smart Citation
“…No enhanced PA was found in the rabbit artery after heating it to 55°C. In this and previous in vitro studies [10,11] using human subendothelium, we found enhanced PA after heating to 55°C and this phenomenon therefore seems to be species-specific. In human specimens, we established that thermally denaturated von Willebrand factor in the subendothelium is responsible not only for a decrease in adhesion after exposure to temperatures high er than 71 °C, but also for an increase in adhesion after exposure to temperatures around 55 °C, provided the von Willebrand factor concentration is low [11], We tentative ly attribute the absence of an increase in adhesion to rab bit artery subendothelium to a high von Willebrand factor content in the subendothelium.…”
Section: Species Differencessupporting
confidence: 85%
“…In several other catheter-based tech niques of arterial revascularization, such as the low-pres sure radio frequency (RF) thermal balloon [4,7,8] or the excimer laser [9], thermal energy is also delivered to the arterial wall. Initial in vitro perfusion studies of thermally damaged vessel wall constituents suggested that heating the arterial wall to temperatures over 70 °C reduces its thrombogcnicity [10][11][12], In vivo animal studies with high-temperature thermal balloon angioplasty, however, show thrombogenicity to be increased [7] or at best equal to conventional balloon angioplasty [13]. Accordingly, clinical results have been disappointing because of an increased restenosis rate, tentatively attributed to exces sive thermal damage of the arterial wall [14].…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments in our laboratory [14], in creased platelet adhesion was observed after exposure to 55 °C. whereas platelet adhesion was much decreased after heating to 90 °C.…”
Section: Platelet Adhesionmentioning
confidence: 61%
“…In a recent in vitro study with human subendothelium in our laboratory, however, the much reduced thrombogenicity after exposure to temperatures above 70 °C was accompanied by a small increase in thrombogenicity after exposure to a temperature of 55 °C [14], The latter increase might interfere with the possible beneficial ef fects of the higher temperatures.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation